Pengembangan Aplikasi Diagnosa Penyakit Mata dengan Algoritma Teorema Bayes - Agustin, Yoga Handoko; Asgara, Zidan; Baswardono, Wiyoga (Jurnal Algoritma, 2024)
The eye is one of the senses that has great importance, because it functions in connection with the surrounding environment. If there are eye problems that are ignored, it will be an early sign of a potentially dangerous eye disorder. As the quality of life decreases and the level of stress received, complaints related to eye disease also increase. Human knowledge and skills are not eternal, they can be lost due to various reasons such as death, retirement, or job changes. When making conclusions, experts may be influenced by certain factors that have the potential to influence the final outcome of that conclusion. So that society can prevent and treat eye diseases, an expert system application is needed to assist eye polyclinic officers and the public in diagnosing eye diseases using the Bayes Theorem inference method. Bayes' theorem is a mathematical equation used to estimate the possibility of future events or their probabilities. This probability refers to the chance of an outcome occurring based on previous information. Its function is to update existing predictions or hypotheses. The results of this research are conclusions about the type of eye disease suffered based on the symptoms chosen by the patient and have been calculated using Bayes calculations. Based on testing 50 patient sample data, the percentage of conformity between the system and experts was 86% of the test data.